Effectiveness of Self-Care Educational Interventions in Patients Undergoing Continuous Ambulatory Peritoneal Dialysis: A Systematic Review - Nurul Hidayah; Masfuri Masfuri; Chiyar Edison (GLOBAL HEALTH SCIENCE GROUP, 2026)
Peritoneal dialysis is a renal replacement therapy that requires patients to perform most of their care independently at home. Lack of patient knowledge, adherence, and skills can increase the risk of complications, such as peritonitis, malnutrition, fluid overload, and reduced quality of life. Educational interventions are an important strategy to improve self-management skills in peritoneal dialysis patients. To determine the effectiveness of educational interventions on knowledge, adherence, self-management, and clinical outcomes in peritoneal dialysis patients. This study used a systematic review design. The reviewed articles included studies on educational interventions for peritoneal dialysis patients, comprising randomized controlled trials and intervention studies. The interventions analyzed included self-care education, dialysis technique retraining, peer support, mobile health applications, problem-based learning, virtual reality, and structured nursing programs. Data were extracted based on author, country, research method, type of educational intervention, and key findings. The systematic literature review was conducted following the PRISMA guidelines by searching four electronic databases (Scopus, ScienceDirect, PubMed, and Taylor & Francis) for English-language articles published between 2020 and 2025. The initial search yielded 7,955 records, of which 24 studies met the eligibility criteria and were included in the final review after the screening and selection process. A total of 10 studies were analyzed. Results indicate that educational interventions generally improve patient knowledge, self-management skills, adherence to diet and fluid restrictions, medication use, hand hygiene, and infection prevention. Retraining with direct supervision has the potential to reduce the risk of peritoneal dialysis-related infections, particularly non-enteric peritonitis and exit site infections. App-based education, peer support, and PBL improve patient engagement, health behaviors, quality of life, and psychosocial support. Furthermore, some interventions have shown improvements in nutritional status, hemoglobin, albumin, fluid management, and blood pressure. However, the impact on overall peritonitis, hospitalization, and patient survival has been inconsistent. Structured, repeated, individualized, and interactive educational interventions effectively improve self-care skills and adherence in peritoneal dialysis patients.